The Cultural Patterns in the Stories of the Quran: The Story of Queen Bilqis as a Model - AbdulHussein, Dr.Alahen Abdulameer (Thi Qar Arts Journal, 2024)
The inspiration for our research stemmed from the verse: “Do they not then reflect on the Quran?” (Quran 4:82). The research was founded on the problem: How can the texts of the Quran be interpreted using the tools of cultural criticism? The aim is to uncover the implicit meanings hidden behind the aesthetic rhetorical meanings. Based on this vision, the Quranic story, as a cultural text and a cognitive manifestation of cultural patterns, contains implicit patterns that reveal the cultural reservoir of the Quran’s renewable energy. This renewal occurs externally through its interaction with its surroundings. The research examined many implicit cultural patterns behind the texts of the Quran in Surah An-Naml.